Pengaruh Penyederhanaan Birokrasi Terhadap Kepuasan Kerja dan Dampaknya Pada Kinerja Pegawai di Lingkup Bps Se- Provinsi Maluku Utara - Arie Pratama; Adnan Rajak; Rahmat Sabuhari (Peneliti.net, 2022)
The purpose of this research is to empirically test and analyze the effect of simplification on employee performance through employee job satisfaction in the BPS Scope of North Maluku Province. The influence discussed is the influence between variables. The research design uses surveys and questionnaires. The population in this study are employees within the BPS of North Maluku Province who have experienced simplification of the bureaucracy (transfer of structural positions to functional positions). In this study, researchers used a sampling technique with a proposive sampling method using a sample of 110 respondents. The data analysis method uses SmartPLS 3.0. The results of the study show that 1) Simplification of the bureaucracy has a positive and significant effect on employee job satisfaction in the Scope of the BPS throughout North Maluku Province, 2) Simplification of the bureaucracy has a positive and significant effect on employee performance in the Scope of BPS throughout North Maluku Province, 3) Job satisfaction has an effect positive and significant impact on employee performance at the Scope of BPS of North Maluku Province, 4) Job satisfaction mediates the effect of bureaucratic simplification on employee performance at the Scope of BPS of North Maluku Province.